Factors Influencing the Utilization of Visual Inspection with Acetic Acid Screening Among Women of Reproductive Age: A Systematic Review - Yendranita, Arfina; Kalsum, Ummi; Ilham, Ilham; Asparian, Asparian; Eka Rini, Willia Novita; Muldiasman, Muldiasman (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Cervical cancer remains a major public health problem, particularly in developing countries, with low participation in early detection through visual inspection with acetic acid screening. Objective: This study aims to identify factors influencing the utilization of visual inspection with acetic acid screening among women of reproductive age. Method: A systematic literature review was conducted using five electronic databases, including PubMed, ScienceDirect, Google Scholar, Directory of Open Access Journals, and Garuda, for articles published between 2020 and 2025. Eligible studies were selected based on predefined criteria, and data were extracted and analyzed using a narrative approach. Result and Discussion: The findings show that screening utilization is influenced by predisposing factors such as knowledge, education, and age; enabling factors including access to health services and availability of information; and reinforcing factors such as support from husbands, families, and health workers. Knowledge was identified as the most dominant factor influencing screening behavior. Conclusion: The utilization of visual inspection with acetic acid screening is determined by the interaction of individual, structural, and social factors, indicating the need for comprehensive strategies to improve screening coverage